FOOD AND FEEDING HABITS OF POLYNEMUS HEPTADACTYLUS CUV. AND VAL. - Kagwade, P V (Indian Journal of Fisheries, 2011)
The food and feeding habits of Polynemus heptadftctylus obtained from Bombayduring the period 1956-58 were studied. Empty stomachs appeared in very high percentagesin both the juveniles and adults all through the year. No period of active feedingat any time of the year was indicated either by the juveniles or adults.P. heptadactylus is carnivorous and its food composition varied widely, crustaceansranking first, followed by fishes, polychaetes, molluscs and echinoderms. Theplanktonic forms, dominated by copepods, were observed in the food of juveniles alone.Crabs, molluscs and echinoderms were absent in the food of juveniles but present in thatof adults. Amongst the crustaceans, Acetes indicus and Squilla spp. dominated in juvenilesand penaeid and carid prawns followed by Squilla spp. in adults. Amongst the fishfood B. macdeltandi ranked high in both the juveniles and adults. The differences in thefood composition of juveniles and adults indicate their habitat preference.